Meconium Peritonitis Connecting the Dots between Pathophysiology, Prenatal Diagnosis and Postnatal Outcome - Meilisva Audila Anggraeni; Budi Wicaksono; Agus Sulistyono (Indonesian Journal of Obstetrics and Gynecology, 2026)
AbstractObjective: To describe the antenatal findings, clinical course, and perinatal outcome of a case of meconium peritonitis.Methods: This is a case report.Case: A 28-year-old primigravida at 34–35 weeks’ gestation was referred for evaluation of hyperechoic fetal bowel. Serial ultrasonography revealed echogenic bowel and fetal ascites without associated major structural anomalies. Maternal serology showed reactive IgG for toxoplasma and cytomegalovirus with high avidity, suggesting past infection. Based on the Zangheri classification, the condition was categorized as grade I meconium peritonitis. The patient delivered at term (38–39 weeks). The female neonate weighed 2,640 g, with a length of 50 cm and APGAR scores of 8 and 9 at 1 and 5 minutes, respectively. Postnatal evaluation revealed no signs of acute abdomen. Babygram findings were unremarkable. The neonate was diagnosed with meconium peritonitis and early-onset sepsis and received empirical antibiotic therapy for 6 days, resulting in clinical improvement.Conclusion: Meconium peritonitis presents with a spectrum of antenatal findings, including intra-abdominal calcifications, ascites, pseudocyst formation, and bowel dilatation. The Zangheri classification is useful for predicting disease severity and the likelihood of postnatal surgical intervention. Mild cases may resolve spontaneously in utero, allowing for favorable outcomes with conservative management and term delivery.Keywords: Meconium peritonitis, prenatal diagnosis, ultrasonography.